Find the best answers to your questions with the help of IDNLearn.com's expert contributors. Our platform offers reliable and comprehensive answers to help you make informed decisions quickly and easily.
Sagot :
To solve this problem, we need to follow a series of steps to calculate the Riemann sum and then determine the limit as [tex]\( n \to \infty \)[/tex].
### Part (a): Riemann Sum Formula
Given the function [tex]\( f(x) = 1 - x^2 \)[/tex] on the interval [tex]\([0,1]\)[/tex]:
1. Divide the interval [tex]\([0,1]\)[/tex] into [tex]\( n \)[/tex] subintervals:
Each subinterval will have width [tex]\( \Delta x = \frac{1-0}{n} = \frac{1}{n} \)[/tex].
2. Right-hand endpoint for [tex]\( c_k \)[/tex]:
The right-hand endpoint for the [tex]\( k \)[/tex]-th subinterval is:
[tex]\[ x_k = a + k \Delta x \][/tex]
Since [tex]\( a = 0 \)[/tex], this becomes:
[tex]\[ x_k = 0 + k \cdot \frac{1}{n} = \frac{k}{n} \][/tex]
3. Formula for the Riemann sum:
The Riemann sum using right-hand endpoints is given by:
[tex]\[ S_n = \sum_{k=1}^{n} f(x_k) \Delta x \][/tex]
Plugging in the given [tex]\( f(x) \)[/tex] and [tex]\( x_k \)[/tex]:
[tex]\[ S_n = \sum_{k=1}^{n} f\left( \frac{k}{n} \right) \Delta x \][/tex]
[tex]\[ S_n = \sum_{k=1}^{n} \left( 1 - \left( \frac{k}{n} \right)^2 \right) \cdot \frac{1}{n} \][/tex]
[tex]\[ S_n = \sum_{k=1}^{n} \left( 1 - \frac{k^2}{n^2} \right) \cdot \frac{1}{n} \][/tex]
[tex]\[ S_n = \sum_{k=1}^{n} \left( \frac{1}{n} - \frac{k^2}{n^3} \right) \][/tex]
[tex]\[ S_n = \sum_{k=1}^{n} \frac{1}{n} - \sum_{k=1}^{n} \frac{k^2}{n^3} \][/tex]
[tex]\[ S_n = \frac{1}{n} \sum_{k=1}^{n} 1 - \frac{1}{n^3} \sum_{k=1}^{n} k^2 \][/tex]
[tex]\[ S_n = 1 - \frac{1}{n^3} \sum_{k=1}^{n} k^2 \][/tex]
Simplifying further, we need the formula for the sum of squares:
[tex]\[ \sum_{k=1}^{n} k^2 = \frac{n(n+1)(2n+1)}{6} \][/tex]
So the Riemann sum formula becomes:
[tex]\[ S_n = 1 - \frac{1}{n^3} \cdot \frac{n(n+1)(2n+1)}{6} \][/tex]
[tex]\[ S_n = 1 - \frac{(n+1)(2n+1)}{6n^2} \][/tex]
### Part (b): Taking the Limit as [tex]\( n \to \infty \)[/tex]
Now, we need to find the limit of [tex]\( S_n \)[/tex] as [tex]\( n \to \infty \)[/tex]:
[tex]\[ \lim_{n \to \infty} S_n = \lim_{n \to \infty} \left( 1 - \frac{(n+1)(2n+1)}{6n^2} \right) \][/tex]
Consider the limit:
[tex]\[ \lim_{n \to \infty} \frac{(n+1)(2n+1)}{6n^2} \][/tex]
[tex]\[ = \lim_{n \to \infty} \frac{2n^2 + 3n + 1}{6n^2} \][/tex]
[tex]\[ = \lim_{n \to \infty} \frac{2 + \frac{3}{n} + \frac{1}{n^2}}{6} \][/tex]
[tex]\[ = \frac{2}{6} = \frac{1}{3} \][/tex]
Thus, we have:
[tex]\[ \lim_{n \to \infty} S_n = 1 - \frac{1}{3} = \frac{2}{3} \][/tex]
So, the area under the curve [tex]\( f(x) = 1 - x^2 \)[/tex] on the interval [tex]\([0,1]\)[/tex] is:
[tex]\[ \boxed{\frac{2}{3}} \][/tex]
Therefore, the final answer for the area under the curve is: [tex]\(\frac{2}{3}\)[/tex].
### Part (a): Riemann Sum Formula
Given the function [tex]\( f(x) = 1 - x^2 \)[/tex] on the interval [tex]\([0,1]\)[/tex]:
1. Divide the interval [tex]\([0,1]\)[/tex] into [tex]\( n \)[/tex] subintervals:
Each subinterval will have width [tex]\( \Delta x = \frac{1-0}{n} = \frac{1}{n} \)[/tex].
2. Right-hand endpoint for [tex]\( c_k \)[/tex]:
The right-hand endpoint for the [tex]\( k \)[/tex]-th subinterval is:
[tex]\[ x_k = a + k \Delta x \][/tex]
Since [tex]\( a = 0 \)[/tex], this becomes:
[tex]\[ x_k = 0 + k \cdot \frac{1}{n} = \frac{k}{n} \][/tex]
3. Formula for the Riemann sum:
The Riemann sum using right-hand endpoints is given by:
[tex]\[ S_n = \sum_{k=1}^{n} f(x_k) \Delta x \][/tex]
Plugging in the given [tex]\( f(x) \)[/tex] and [tex]\( x_k \)[/tex]:
[tex]\[ S_n = \sum_{k=1}^{n} f\left( \frac{k}{n} \right) \Delta x \][/tex]
[tex]\[ S_n = \sum_{k=1}^{n} \left( 1 - \left( \frac{k}{n} \right)^2 \right) \cdot \frac{1}{n} \][/tex]
[tex]\[ S_n = \sum_{k=1}^{n} \left( 1 - \frac{k^2}{n^2} \right) \cdot \frac{1}{n} \][/tex]
[tex]\[ S_n = \sum_{k=1}^{n} \left( \frac{1}{n} - \frac{k^2}{n^3} \right) \][/tex]
[tex]\[ S_n = \sum_{k=1}^{n} \frac{1}{n} - \sum_{k=1}^{n} \frac{k^2}{n^3} \][/tex]
[tex]\[ S_n = \frac{1}{n} \sum_{k=1}^{n} 1 - \frac{1}{n^3} \sum_{k=1}^{n} k^2 \][/tex]
[tex]\[ S_n = 1 - \frac{1}{n^3} \sum_{k=1}^{n} k^2 \][/tex]
Simplifying further, we need the formula for the sum of squares:
[tex]\[ \sum_{k=1}^{n} k^2 = \frac{n(n+1)(2n+1)}{6} \][/tex]
So the Riemann sum formula becomes:
[tex]\[ S_n = 1 - \frac{1}{n^3} \cdot \frac{n(n+1)(2n+1)}{6} \][/tex]
[tex]\[ S_n = 1 - \frac{(n+1)(2n+1)}{6n^2} \][/tex]
### Part (b): Taking the Limit as [tex]\( n \to \infty \)[/tex]
Now, we need to find the limit of [tex]\( S_n \)[/tex] as [tex]\( n \to \infty \)[/tex]:
[tex]\[ \lim_{n \to \infty} S_n = \lim_{n \to \infty} \left( 1 - \frac{(n+1)(2n+1)}{6n^2} \right) \][/tex]
Consider the limit:
[tex]\[ \lim_{n \to \infty} \frac{(n+1)(2n+1)}{6n^2} \][/tex]
[tex]\[ = \lim_{n \to \infty} \frac{2n^2 + 3n + 1}{6n^2} \][/tex]
[tex]\[ = \lim_{n \to \infty} \frac{2 + \frac{3}{n} + \frac{1}{n^2}}{6} \][/tex]
[tex]\[ = \frac{2}{6} = \frac{1}{3} \][/tex]
Thus, we have:
[tex]\[ \lim_{n \to \infty} S_n = 1 - \frac{1}{3} = \frac{2}{3} \][/tex]
So, the area under the curve [tex]\( f(x) = 1 - x^2 \)[/tex] on the interval [tex]\([0,1]\)[/tex] is:
[tex]\[ \boxed{\frac{2}{3}} \][/tex]
Therefore, the final answer for the area under the curve is: [tex]\(\frac{2}{3}\)[/tex].
Your presence in our community is highly appreciated. Keep sharing your insights and solutions. Together, we can build a rich and valuable knowledge resource for everyone. Your questions find answers at IDNLearn.com. Thanks for visiting, and come back for more accurate and reliable solutions.